Cold temperature characterization of ring triplets based on RD53A readout chip. (1st November 2022) - Samy, M.A.A.; Sultan, D.M.S.; Lapertosa, A.; Gariano, G.; Dalla Betta, G.-F.
Abstract: This paper reports the Trento test setup and the cold test procedure for three triplets (ID: R4, R5, and R6) assembled with RD53A readout cheap and planar sensors. The trim and tuning of Front Ends (FE), as well as sensor I - V measurements, were made for a cold temperature (−25 °C) for an applied voltage (−30 V for R4, −10 V for R5 and R6). As a part of QC, initially, several test scans: analog, digital, threshold, ToT, noise, etc., were performed to evaluate the module response at −25 °C before applying a necessary tuning script to find a spatially uniform threshold distribution over the pixel matrix. Later, the crosstalk-based disconnected-bump and X-ray scans were made to check modules' bump bonding quality and hits per pixel. Results reported here show a good agreement to a qualified triplet module, assuring the Trento cold test setup capacity for the ATLAS ITk QA/QC process.